The adverse effect of heat stress and potential nutritional interventions. Issue 18 (30th August 2022) - Chen, Xinwei; Liu, Wanlu; Li, He; Zhang, Jian; Hu, Changli; Liu, Xinqi
Abstract : Protein, vitamin, trace element and electrolyte can mitigate heat damage by enhancing the antioxidant system and immune function, promoting heat shock protein expression, and suppressing inflammatory responses. Abstract : Heat stress can cause tissue damage and metabolic disturbances, including intestinal and liver dysfunction, acid–base imbalance, oxidative damage, inflammatory response, and immune suppression. Serious cases can lead to heatstroke, which can be life-threatening. The body often finds it challenging to counteract these adverse effects, and traditional cooling methods are limited by the inconvenience of tool portability and the difficulty of determining the cooling endpoint. Consequently, more research was conducted to prevent and mitigate the negative effect of heat stress via nutritional intervention. This article reviewed the pathological changes and altered metabolic mechanisms caused by heat stress and discussed the protein (amino acid), vitamin, trace element, and electrolyte action pathways and mechanisms to mitigate heat stress and prevent heat-related disease. The main food sources for these nutrients and the recommended micronutrient supplementation forms were summarized to provide scientific dietary protocols for special populations.